2015
DOI: 10.1167/iovs.14-16087
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Role of TLR2 and MyD88 Signaling in Eliciting Innate Immune Responses in Staphylococcal Endophthalmitis

Abstract: TLR2 and MyD88 signaling plays an important role in protecting the retina from staphylococcal endophthalmitis by production of the antimicrobial peptide CRAMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 48 publications
5
77
0
1
Order By: Relevance
“…Our MyD88 data agree with those of Talreja et al, who recently reported on the importance of MyD88 in experimental S. aureus endophthalmitis (41). There was a significant reduction of inflammatory cell influx in MyD88 Ϫ/Ϫ and TRIF Ϫ/Ϫ eyes, likely due to significantly decreased concentrations of proinflammatory mediators in these eyes compared to those in C57BL/6J controls.…”
Section: C57bl/6j and Tlr4supporting
confidence: 92%
See 1 more Smart Citation
“…Our MyD88 data agree with those of Talreja et al, who recently reported on the importance of MyD88 in experimental S. aureus endophthalmitis (41). There was a significant reduction of inflammatory cell influx in MyD88 Ϫ/Ϫ and TRIF Ϫ/Ϫ eyes, likely due to significantly decreased concentrations of proinflammatory mediators in these eyes compared to those in C57BL/6J controls.…”
Section: C57bl/6j and Tlr4supporting
confidence: 92%
“…*, P Յ 0.036. ular environment in TRIF Ϫ/Ϫ mice. Talreja et al (41) recently reported that a deficiency in cathelicidin-related antimicrobial peptide (CRAMP) led to an increased S. aureus burden in mouse eyes with endophthalmitis, so it would be reasonable to speculate that increased levels of AMP would lead to a lower bacterial burden. However, Stockinger et al (42) reported that TRIF Ϫ/Ϫ mice had low AMP expression levels but in the intestine.…”
Section: Fig 9 Proinflammatory Mediator Expression In Tlr4mentioning
confidence: 99%
“…Parkunan et al (2015) reported that mice deficient in MyD88, the intracellular adapter molecule for several TLRs, had significantly delayed intraocular inflammation than wild type mouse eyes infected with B. cereus . Similar findings were reported for S. aureus in MyD88-deficient mice (Talreja et al, 2015). Surprisingly, deficiencies in Toll/IL-1 receptor domain-containing adapter-inducing interferon β (TRIF, the intracellular adaptor molecule for TLR4) and in TLR4 itself also resulted in significantly less intraocular inflammation during experimental B. cereus endophthalmitis, suggesting that MyD88-independent pathways were involved in the intraocular response to B. cereus and that B. cereus may harbor ligands for TLR4 which instigate intraocular inflammation (Parkunan et al, 2015).…”
Section: Experimental Models: Therapeutics and Virulencesupporting
confidence: 90%
“…TLR2 is also important in mediating inflammation in Staphylococcus aureus endophthalmitis (Kochan et al, 2012 and Talreja et al, 2015). We do not know whether the pili of Bacillus interact with these innate immune receptors and are, in fact, TLR ligands.…”
Section: Discussionmentioning
confidence: 99%